Investigation of hemostasis by thromboelastography in the patient with liver cirrhosis (Clinical case) - Ye. L. Bulanova; A. Yu. Bulanov; D. S. Gatsolayeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. The control of hemostasis is important investigation in clinical practice. The differential diagnosis between surgical and coagulopathic nature of bleeding after the invasive intervention helps to choose optimal algorithm of patient management. Presented clinical case illustrates approach to investigation and treatment of such patients.Original positions. Patient K., male 54 years was hospitalized to the clinic for decompensated liver cirrhosis of toxic and viral etiology. Due to high severity of patient’s state he was directed to intensive care unit. Intravenous infusion therapy required installation of central venous catheter, that was complicated by catheter bleeding. Application of thromboelastography helped to differentiate disorder of systemic hemostasis from mechanical damage of blood vessels at catheterization. Coagulopathic nature of complication has been confirmed. Dynamic control of thromboelastography allowed to estimate efficacy of transfusion therapy and to plan ways of its correction.Conclusion. Estimating the submitted clinical case, it is possible to conclude on necessity of thromboelastography in patients with bleeding, which can develop both due to disorder of hemostasis (at patients with failure of protein-synthetic liver function), and due to invasive intervention. Data of thromboelastography help to adjust hemostatic treatment adequately and to avoid additional tests, and, probably, surgical interventions.